2002
DOI: 10.1002/cncr.10981
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of a prospective policy of margin‐directed radiation dose escalation in breast‐conserving therapy

Abstract: BACKGROUND A prospectively applied treatment policy for breast‐conserving therapy used margin assessment as the exclusive guide to the intensity of radiation therapy directed at the tumor bed. METHODS From 1982 to 1994, 498 women with 509 Stage I/II breast carcinomas with a median follow‐up of 121 months were treated. Final margin status (FMS) categories were defined as greater than 5 mm, greater than 2–5 mm, greater than 0–2 mm, and positive. For margins less than or equal to 2 mm or indeterminate, reexcision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 36 publications
0
48
0
3
Order By: Relevance
“…In addition to the data above, in younger breast cancer patients the rate of axilla positivity and HG were higher, ER and PR positivity were lower and HER-2 positivity was also higher (17)(18)(19)(20). In our database, in patients under 40 years of age pN0 was 44%, HGIII rate was 60%, ER positivity was 61%, PR positivity was 57%, and HER-2 positivity was 26.5%, while in the more advanced aged group pN0 was 60%, HG3 rate was 44%, ER positivity was 71%, PR positivity was 59%, and HER-2 positivity was 23%.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to the data above, in younger breast cancer patients the rate of axilla positivity and HG were higher, ER and PR positivity were lower and HER-2 positivity was also higher (17)(18)(19)(20). In our database, in patients under 40 years of age pN0 was 44%, HGIII rate was 60%, ER positivity was 61%, PR positivity was 57%, and HER-2 positivity was 26.5%, while in the more advanced aged group pN0 was 60%, HG3 rate was 44%, ER positivity was 71%, PR positivity was 59%, and HER-2 positivity was 23%.…”
Section: Discussionmentioning
confidence: 70%
“…146 The ability to achieve negative surgical margins before radiation has been identified as the most consistent factor associated with a low risk for local recurrence. 136,138,139,[147][148][149][150][151][152][153] Kurtz et al reported a 5-year local recurrence in 6% of patients with negative margins and 23% for positive margins. 136 Heimann et al reported a 5-year local recurrence in 2% with negative versus 11% with positive margins.…”
Section: Smentioning
confidence: 99%
“…Young patient age was also a factor linked with increased local recurrence after BCS and radiation. 136,139,141,[152][153][154] This was suspected to be because of other adverse features in younger patients, such as EIC and high-grade disease. 136 Haffty et al reported that mammographically detected breast cancer had a trend to improved local control rates with breast-conserving surgery and radiation compared with palpable breast cancers.…”
Section: Smentioning
confidence: 99%
See 2 more Smart Citations